Kapok (Ceiba Pentandra (L.) Fiber for Removal of Spilled Oil - Daud, Amir Haidhar; Hussin, Rosniza (Progress in Engineering Application and Technology, 2023)
Kapok is a natural cellulosic fiber with unique characteristics. It is often considered the most effective method for cleaning up and collecting oil spills. A critical investigation was conducted to study the potential of kapok fiber as sorbent material. This research aims to analyze the surface properties of kapok fiber for the ability of kapok fiber to absorb oil and evaluate the interaction mechanisms of kapok fiber in oil/water as oil sorbent. Therefore, the surface properties of kapok fiber were characterization and analyzed using Scanning Eelectron Microscope, Fourier Transform Infrared and contact angle. To investigate the selectivity nature and the sorption capacity of 5 g kapok fiber and different types of oil were used. The types of oil used are 60ml of original palm oil, 60ml of used palm oil, 60ml of original coconut oil and 60ml of used coconut oil. Kapok fiber was able to absorb all the types of oil, with original palm oil, the oil absorbs the shortest time with a record of 15 minutes compared to other oils. Scanning electron microscopy (SEM) was used to examine the morphology of raw kapok fiber. In this study, kapok fiber was shown to have a porous hollow lumen structure and a waxy coating on the surface. Other than that, for the contact angle analysis show that the kapok fiber had high water contact angle up to 137.30 ̊. The water droplet was stood on the kapok fibers surfaces before and after absorption with the range of contact angles from 102 ̊ to 137 ̊. In contrast, the oil droplet had disappeared from the surfaces of kapok fiber within a few seconds. This review discusses the recent papers on the use of natural fiber sorbent for removal of oil from water. With their excellent oil removal properties, environmental friendliness, easy availability, and feasibility, natural fibrous sorbents are an attractive alternative for oily wastewater treatment.